COMPARISON OF THE IMPLEMENTATION OF THE 2013 CURRICULUM AND THE MERDEKA CURRICULUM IN INDONESIAN SCHOOLS: A LITERATURE REVIEW ON THE TRANSITION PERIOD TOWARDS A SINGLE NATIONAL CURRICULUM - Abdul Wahab Syakhrani (Indonesian Journal of Education (INJOE), 2025)
This study is a literature review that discusses the comparison of the implementation of the 2013 Curriculum and the Merdeka Curriculum in Indonesian schools during the transition period towards a single national curriculum. The background of this study is based on the dynamics of national curriculum changes that aim to improve the quality of education and adapt education to the needs of the times. The study aims to analyse the main similarities and differences between the 2013 Curriculum, known for its standardised structure, thematic learning, and administrative assessment, and the Merdeka Curriculum, which offers flexibility, character development through the Pancasila Student Profile, project-based learning, and more reflective assessment. The research method used is a literature review with content analysis of relevant literature, policy documents, and research findings. The results indicate that the 2013 Curriculum emphasizes the regularity and uniformity of the learning process, while the Merdeka Curriculum provides greater freedom for innovation, educational autonomy, and a focus on character development and critical thinking skills among students. The transition to a single national curriculum presents challenges in terms of resource readiness, teacher training, and differences in infrastructure and understanding across regions. The research conclusions emphasise the importance of socialisation, equitable training, and policy support during the transition process to ensure that national educational goals are achieved optimally across all educational institutions.